Fisheries centres in Solomon Islands - Tua, Paul; Buga, Ben; Eriksson, Hampus (Ministry of Fisheries and Marine Resources, 2024)
This brief report presents the summary of a snapshot assessment by MFMR together with Provincial Fisheries Officers (PFOs) during the national PFO annual conference in 2022, and a follow-up validation with PFOs in 2023. The goal was to create a snapshot of locations, services, and the status of the centres in each of the provinces, providing a national overview. This work is part of ongoing research to better understand costs and benefits from livelihood investments.